Chemical and physical characterization of fresh-cut ’Ágata’ potatoes packed under different active modified atmospheres - Pineli, Lívia Lacerda Oliveira; moretti, Celso Luiz; Almeida, Gustavo Costa; Onuki, Ana Cecília Amorim; Nascimento, Aline Bum Gomes (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to evaluate chemical and physical characteristics of fresh-cut 'Ágata' potatoes packed under different active modified atmospheres, during refrigerated storage. 'Ágata' potatoes were minimally processed as baby potatoes and packed in nylon multilayer films. The treatments applied were partial vacuum, and atmospheres with 10%CO2, 2%O2, 88%N2 and 5%CO2, 5%O2, 90%N2. After that, they were stored at 5ºC. Every three days, tubers were evaluated for browning index, polyphenoloxidase and peroxidase activity, firmness, total soluble solids, and titratable acidity. Storage under partial vacuum was the best treatment to control browning and to reduce polyphenoloxidase and peroxidase activities as well as to prevent reduction of total soluble solids, loss of firmness, accumulation of water inside the package and higher titratable acidity. Active modified atmospheres showed faster and sharper browning development, increase of firmness due to tubers dehydration, increase in total soluble solids and lower acidity development comparing with tubers stored under partial vacuum. Storage under partial vacuum showed the best results for maintaining the quality of fresh cut baby potatoes. However, other treatments to maintain firmness freshness, without the development of off-flavors and browning, should be evaluated.